Implementasi dan Pengujian Tahanan Isolasi pada Transformator Distribusi 200 kVA di PT. PLN (PERSERO) UP3 Pekanbaru - Rianto, Bayu; Chrismondari (Jurnal Indragiri Penelitian Multidisiplin, 2025)
Power transformers are high-voltage equipment that function to distribute electrical power, either from high voltage to low voltage or vice versa. However, if the insulation condition of the transformer experiences a decrease in quality, this can cause operational failure, even more serious damage that disrupts the electrical system as a whole. To prevent this, testing of the insulation resistance is required. One of the methods used to test this insulation condition is the polarization index method. This method is considered the most accurate and effective way to assess the feasibility of insulation resistance in transformers, especially those located in substations and distribution substations in Indonesia. This study was conducted by taking data from the location of PT. PLN (Persero) UP3 Pekanbaru. Through insulation resistance testing, the results of the measurement of the polarization index value were obtained. The data collected were then calculated and analyzed to obtain more optimal evaluation results. The results show that the polarization index value on the primary ground is at 1.25 and the secondary ground is 1.5. Both values ​​are still in the good category, referring to the standard polarization index value which ranges from 1.25 to 2.0